Asymptotic behavior toward the combination of contact discontinuity with rarefaction waves for 1-D compressible viscous gas with radiation. (June 2017) - Hong, Hakho
Abstract: This paper is concerned with the large-time behavior toward the combination of two rarefaction waves and viscous contact wave for the Cauchy problem to a one-dimensional Navier–Stokes–Poisson coupled system, modeling the dynamics of a viscous gas in the presence of radiation. We show that the composite wave with small strength is asymptotically stable under partially large initial perturbations. The proofs are based on the more refined energy estimates to control the possible growth of the perturbations induced by two different waves and large data.